Students’ Evaluation of Live Online Lectures Versus Pre-Recorded Video Lectures During COVID-19: Focusing on Students’ Study Behaviors - Eun Jung Kim; Mi Jeong Kim (SAGE Open)
This study aimed to investigate university students’ evaluations of pre-recorded video and live online lectures, focusing on the factors that influence these assessments, particularly students’ studying behaviors. We conducted a web-based survey to gather data from undergraduate students. The results revealed that students rated live online lectures higher than pre-recorded video lectures in learning efficiency, student–teacher connectivity, and student–student connectivity. However, a contrasting trend was observed for academic performance. The multivariate analysis indicated that students who reported higher levels of restraint from distractions while listening to online lectures evaluated both pre-recorded video and live online lectures significantly more favorably. Moreover, students who regularly turned on their cameras during live lectures tended to rate online lectures more positively. These findings underscore the significance of students’ studying behavior as a critical factor influencing the effectiveness and outcomes of online lectures. It is important to foster and encourage students’ active engagement with online lectures and promote the development of self-learning skills.